Mitochondrial modulators for bipolar disorder: A pathophysiologically informed paradigm for new drug development. (January 2013) - Nierenberg, Andrew A; Kansky, Christine; Brennan, Brian P; Shelton, Richard C; Perlis, Roy; Iosifescu, Dan V
Objectives: Bipolar patients frequently relapse within 12 months of their previous mood episode, even in the context of adequate treatment, suggesting that better continuation and maintenance treatments are needed. Based on recent research of the pathophysiology of bipolar disorder, we review the evidence for mitochondrial dysregulation and selected mitochondrial modulators (MM) as potential treatments. Methods: We reviewed the literature about mitochondrial dysfunction and potential MMs worthy of study that could improve the course of bipolar disorder, reduce subsyndromal symptoms, and prevent subsequent mood episodes. Results: MM treatment targets mitochondrial dysfunction, oxidative stress, altered brain energy metabolism and the dysregulation of multiple mitochondrial genes in patients with bipolar disorder. Several tolerable and readily available candidates include N -acetyl-cysteine (NAC), acetyl-L-carnitine (ALCAR), S -adenosylmethionine (SAMe), coenzyme Q10 (CoQ10), alpha-lipoic acid (ALA), creatine monohydrate (CM), and melatonin. The specific metabolic pathways by which these MMs may improve the symptoms of bipolar disorder are discussed and combinations of selected MMs could be of interest as well. Conclusions: Convergent data implicate mitochondrial dysfunction as an important component of the pathophysiology of bipolar disorder. Clinical trials of individual MMs as well as combinations are warranted.